1998
DOI: 10.1046/j.1464-410x.1998.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen velocity as a measure of the natural history of prostate cancer: defining a ‘rapid riser’ subset

Abstract: Objective  To study the rate of change in prostate specific antigen (PSA velocity) in patients with prostate cancer initially managed by ‘watchful waiting’. Patients and methods  Serial PSA levels were determined in 141 patients with prostate cancer confirmed by biopsy, who were initially managed expectantly and enrolled between May 1990 and December 1995. Sixty‐seven patients eventually underwent surgery (mean age 59 years) because they chose it (the decision for surgery was not based on PSA velocity). A coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
0
26
2
Order By: Relevance
“…However, others [5,6,10] reported no correlation between T d and any other variables, including clinical stage. Schmid et al [7] reported in a series of 43 patients that there was a statistically significant relationship between a Gleason score of £ 6 vs ≥ 7 and T d of > 24 vs £ 24 months ( P = 0.05).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, others [5,6,10] reported no correlation between T d and any other variables, including clinical stage. Schmid et al [7] reported in a series of 43 patients that there was a statistically significant relationship between a Gleason score of £ 6 vs ≥ 7 and T d of > 24 vs £ 24 months ( P = 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…The median (range) follow-up of the cohort was 45 (6-85) months and the median number of PSA measurements for calculating T d was 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The distribution of the frequency of PSA measurements was 3-5 in The distribution of l and the corresponding T d for the 231 patients is shown in Table 3; the median (range) T d was 7.0 (0.51-infinity).…”
Section: Resultsmentioning
confidence: 99%
“…It has been speculated that tumors with relatively stable or declining PSA levels may be in their linear phase of growth and may safely be followed for years without treatment. 6,8,17, Conversely, tumors with rapidly increasing PSA levels may be in the exponential growth phase and thus signi®cant. The median calculated PSA doubling time in patients with increasing levels was 25.8 months in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on PSA kinetics, such as the PSA doubling time (PSADT), PSA slope, and PSA velocity (2)(3)(4), have indicated that these may provide valuable information for diagnosis and staging. The estimation of PSA kinetics, such as PSADT, is not difficult; however, finding an important enough reason to wait for >3 months to measure PSADT for staging prior to making a decision regarding the treatment strategy is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of PSA kinetics, such as PSADT, is not difficult; however, finding an important enough reason to wait for >3 months to measure PSADT for staging prior to making a decision regarding the treatment strategy is difficult. Additionally, the prognostic values with respect to PSA recurrence and cancer-specific mortality remain controversial (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%